Temporal and spatial variation of sea surface temperature, chlorophyll a, and primary productivity in the Gulf of California - Fátima Escalante; José Eduardo Valdez-Holguín; Saúl Álvarez-Borrego; José Rubén Lara-Lara (Ciencias Marinas, 2013)
Using satellite derived data from 1997–2010, sea surface temperature (SST), chlorophyll a (Chl) and primary productivity (PP) variations are described at different temporal and spatial scales in the Gulf of California. Interannual signals of El Niño (EN) and La Niña (LN) were more evident at the entrance to the gulf. Once EN or LN events were over, there was a delayed response of three to six months for the reestablishment of “normal” phytoplankton activity levels. Phytoplankton response to high concentrations of nutrients due to LN was not immediate. At regional scale, EN significantly decreased the Chl mean with regard to “normal” conditions at the entrance, central gulf, and Midriff Islands region (MIR); however, PP under EN conditions decreased significantly only at the entrance. The increase in Chl and PP due to LN relative to “normal” conditions was significant only at the entrance. SST, Chl, and PP annual signals are the main source of variation, particularly for the central gulf and entrance, but in the MIR, “winter” PP (1.96 g C m–2 d–1) was not significantly different from that of “summer” (1.62 g C m–2 d–1). Highest PP was found in the central gulf and MIR, where inferences of production attributable to new production were estimated at more than 60% of PP. At the gulf entrance, primary productivity was mainly attributable to regenerated production, particularly during summer and autumn.